Staring us in the face? An embodied theory of innate face preference. Issue 6 (20th June 2014) - Wilkinson, Nick; Paikan, Ali; Gredebäck, Gustaf; Rea, Francesco; Metta, Giorgio
Abstract Human expertise in face perception grows over development, but even within minutes of birth, infants exhibit an extraordinary sensitivity to face‐like stimuli. The dominant theory accounts for innate face detection by proposing that the neonate brain contains an innate face detection device, dubbed 'Conspec'. Newborn face preference has been promoted as some of the strongest evidence for innate knowledge, and forms a canonical stage for the modern form of the nature–nurture debate in psychology. Interpretation of newborn face preference results has concentrated on monocular stimulus properties, with little mention or focused investigation of potential binocular involvement. However, the question of whether and how newborns integrate the binocular visual streams bears directly on the generation of observable visual preferences. In this theoretical paper, we employ a synthetic approach utilizing robotic and computational models to draw together the threads of binocular integration and face preference in newborns, and demonstrate cases where the former may explain the latter. We suggest that a system‐level view considering the binocular embodiment of newborn vision may offer a mutually satisfying resolution to some long‐running arguments in the polarizing debate surrounding the existence and causal structure of newborns' 'innate knowledge' of faces.